RURAL FARMERS’ ATTITUDE TO INDIGENOUS KNOWLEDGE SHARING FOR SELECTED LIVELIHOOD ACTIVITIES IN SOUTH-SOUTH NIGERIA - Ominikari, Abraham Godwin; Wasini, Dobie Allen (FUDMA JOURNAL OF SCIENCES, 2022)
The study assessed rural farmers’ attitude to indigenous knowledge sharing for selected livelihood activities in South-South Nigeria. Multi-stage sampling was used to select 360 farmers. Data collection was through questionnaire and analyzed using descriptive and inferential statistics such as mean and Analysis of variance (ANOVA). The result reveals that sharing between two or more farmers ( = 3.9), parents/guardian/friends ( = 3.8), participation ( = 3.8), observation ( = 3.7), farmer’s groups ( = 3.7), demonstration ( = 3.4), social group gathering ( = 3.4), village groups/age grades ( = 3.4), village meetings ( = 3.4), women meetings ( = 3.3) and apprenticeship ( = 3.0) were the major ways farmers share knowledge. Furthermore, cost intensive to undertake ( = 2.56), time consuming to undertake ( = 2.52), not valued by farmers ( = 2.07) and very labourious to undertake ( = 1.78) were some of the mean responses of farmers on their attitude to knowledge sharing. The ANOVA result showed no significant difference in the mean ratings of the respondents on their attitude to indigenous knowledge sharing for selected livelihood activities in South-South Nigeria at 5% level of significance. From the findings, it was concluded that farmers generally had unfavourable attitude towards indigenous knowledge sharing for selected livelihood activities. The study recommended that the State Ministries of Agriculture and Extension Agencies should assist the rural farmers by organizing demonstrations and coordinating farmer groups which would enable them share their indigenous knowledge for better livelihood activities in the study area.